German-Sino Business Networks: Using Organized Networks to Develop Business with China - Häntzschel, Alexander (Springer, 2015)
In this book, Alexander Häntzschel presents the benefits of organized networks and provides a first-ever overview of German-Sino business networks. Based on more than 20 expert interviews and research of 30 different cases, the analysis covers the different forms of organization, their target groups and members, services and activities, and accessibility and membership fees. Complementary to the analysis, the results of a survey bring forward the experiences and expectations of professionals involved in such networks. With this Springer Brief, business professionals get a quick and useful overview of the leading networks such as the German Asia-Pacific Business Association, the German-Chinese Business Association, and the Asian Social Business Community